The Idiosyncratic Volatility Puzzle: Time Trend or Speculative Episodes? - Brandt, Michael W.; Brav, Alon; Graham, John R.; Kumar, Alok (Review of Financial Studies, 2010)
[Campbell, Lettau, Malkiel, and Xu (2001) document a positive trend in idiosyncratic volatility during the 1962-1997 period. We show that by 2003 volatility falls back to pre-1990s levels. Furthermore, we show that the increase and subsequent reversal is concentrated among firms with low stock prices and high retail ownership. This evidence suggests that the increase in idiosyncratic volatility through the 1990s was not a time trend but, rather, an episodic phenomenon, at least partially associated with retail investors. Results from cross-sectional regressions, conditional trend estimation, stock-split events, and "attentiongrabbing" events are consistent with a retail trading effect.]